Design of Infak Payment Information System Using Borland Delphi 7 (Case Study: Aceh Energy & Mineral Resources Department) - Marhamah, Ida; Syafrinal; Iqbal, Taufiq; Ihsanuddin (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2022)
The purpose of the study is to create an Infaq Payment Information System using Delphi 7 to make Infak Data Payments contained in the Aceh Energy and Mineral Resources Office where there are advantages when compared to Microsoft Excel in terms of Infaq Payments including in terms of Output, where the system that will be the author developed can load more than one Output. In the process of the author's research regarding infaq payments at the aceh energy and mineral resources service, in the current system there are often obstacles or problems that arise. This happens because there are several things that quite interfere with the Financial Monitoring process, including; The length of the infaq payment process is one of the main obstacles, the use of microsoft excel is considered too complicated in terms of input, processing, information, the process of accessing / uploading data will take longer and waste more energy, and the possibility of errors or mistakes is more risky due to everything something that can manually interfere with the accuracy of the user. In application development, the researcher uses the prototype method. From the results of the research, the calculation application can be used as payment at the Aceh Energy & Mineral Resources Department and is designed using Delphi, then the results of the evaluation of the current desktop application display with prototype design are known that each category has an increase in usability value. Content, Organization and Readability previously had a value of 0.61 and increased to 0.66. The Navigation category was previously 0.62 to 0.67. The previous User Interface Design category was 0.63 to 0.70 and the previous Performance and Effectiveness category was 0.64 to 0.72.